IMPLEMENTASI KEBIJAKAN PENGELOLAAN KURIKULUM DI SEKOLAH DASAR - Handayani, Fitri; Martinopa, Lindri; Perdana, Andika Surya; Gistituati, Nurhizrah; Rusdinal, Rusdinal (Study program PGSD FKIP Universitas Bung Hatta, 2022)
This study aims to explain the policies and curriculum in elementary schools that focus on provisions in curriculum management, curriculum scope, functions and implementation in elementary schools. Policies on the curriculum are related to the provisions or rules that will be set against the wishes of national education. Management of the curriculum is the same as strategies, efforts or efforts designed jointly by leaders in their fields to improve the quality of education. Besides that, it can also produce a learning productivity for children, there is a reciprocal relationship between individuals and groups. The management/management of the 2013 curriculum aims to improve the competence of students and find out the problems of implementing the 2013 curriculum. This activity is carried out through 3 stages, namely planning, implementation and evaluation/evaluation. The third stage affects children's education, what is planned will have an impact on children as subjects who will implement the curriculum. This research uses a case study or literature study approach. This article was written by reviewing 25 journals related to curriculum management policies. Researchers describe the findings of the phenomena that occur in the field using observation techniques. The results of the study indicate that curriculum management must be carried out as well as possible so that the resulting output has a good impact. Each school gives different results in this management. This can be seen from all aspects of what is done at school.